Penentuan Daerah Perlindungan Batang Petir - Bayu Purnomo; T. Haryono (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2015)
External lightning protection system consisting of a finial, down-conductor and grounding are important aspects in the installation of lightning rods. The study was conducted by using a finial rod copper that aims to study the protection angle of a lightning rod. High finial of the earth would determine the angle of protection desired. Based on this research, the object of protection is the angle between 85,6° - 89,3°. This suggests that a lightning rod has limitations in protecting an area. The larger the area to be protected, the more number of lightning rod needed.